Jesus Kristus-Guds Ord - Fibiger, Ebbe (Grundtvig-Studier, 1977)
Jesus Christ - God's Word by Ebbe Fibiger One of the most characteristic traits in Grundtvig’s ministry as preacher and hymn-writer is his use of the expression “God’s Word” as a name for Christ. God created the world through the Word. He let the Word dwell among people through Jesus Christ, and He creates what is now amongst us through the Word. Creation and Redemption through the Word - these are the major elements in Grundtvig’s theology. The place where Redemption occurs is the Church. It is here that Jesus is born and resurrected in the Word. This theology links up with Grundtvig’s use, from 1823 onwards, of the expression, “The Word is Life and Spirit”. This means at least two things: that the Word as the Word of Life triumphs over death (that is, the death of man); and that the Word as Spirit brings God’s Kingdom closer through the Church. However, it is Jesus’ concrete Words that have the quality of being “Life and Spirit”. Grundtvig fastens on the imperatives with which Jesus makes things happen. For example, ‘effata’, (be opened) to the deaf and dumb man (Mark 7:34), ‘Weep not’ to the widow of Nain (Luke 7:13) and ‘Peace’ to the disciples after the resurrection (e.g. John 20:21). With these words Jesus acts from power. This power is felt most powerfully, however, in the words of the rituals: in the questions and answers of the creed, in the words of baptism, in the Lord’s Prayer and the blessing of peace at baptism, and in the words of the Eucharist. There are similarities but also differences between the ritual words and the non-ritual. The common link is that in particular the Words are a means of power, but whereas the Words of the Eucharist and baptism take effect with no conditions attached, the Words heard in the rest of the Church’s witness only take effect on condition that the human heart believes. We can learn from Grundtvig not to say “only the Word”. His theology of the Word puts a capital W on the word, for the theology of the Word is not just word-play.